Impact of aetiological treatment on conventional and multiplex serology in chronic Chagas disease. - Rodolfo Viotti; Carlos Vigliano; María Gabriela Alvarez; Bruno Lococo; Marcos Petti; Graciela Bertocchi; Alejandro Armenti; Ana María De Rissio; Gretchen Cooley; Rick Tarleton; Susana Laucella (Public Library of Science (PLoS), 2011)
The main criterion for treatment effectiveness in Chagas Disease has been the seronegative conversion, achieved many years post-treatment. One of the main limitations in evaluating treatment for chronic Chagas disease is the lack of reliable tests to ensure parasite clearance and to examine the effects of treatment. However, declines in conventional serological titers and a new multiplex assay can be useful tools to monitor early the treatment impact.Changes in antibody levels, including seronegative conversion as well as declines in titers, were serially measured in 53 benznidazole-treated and 89 untreated chronic patients in Buenos Aires, Argentina with a median follow-up of 36 months. Decrease of titers (34/53 [64%] treated vs. 19/89 [21%] untreated, p<0.001) and seronegative conversion (21/53, [40%] treated vs. 6/89, [7%] untreated, p<0.001) in at least one conventional serological test were significantly higher in the benznidazole-treated group compare with the untreated group. When not only complete seronegative conversion but also seronegative conversion on 2 tests and the decreases of titers on 2 or 3 tests were considered, the impact of treatment on conventional serology increased from 21% (11/53 subjects) to 45% (24/53 subjects). A strong concordance was found between the combination of conventional serologic tests and multiplex assay (kappa index 0.60) to detect a decrease in antibody levels pos-treatment.Treatment with benznidazole in subjects with chronic Chagas disease has a major impact on the serology specific for T. cruzi infection in a shorter follow-up period than previously considered, reflected either by a complete or partial seronegative conversion or by a significant decrease in the levels of T. cruzi antibodies, consistent with a possible elimination or reduction of parasite load.